Prevalence study of genetically defined skeletal muscle channelopathies in England - Horga, Alejandro (Lippincott Williams & Wilkins, 2013)
OBJECTIVES: To obtain minimum point prevalence rates for the skeletal muscle channelopathies and to evaluate the frequency distribution of mutations associated with these disorders. METHODS: Analysis of demographic, clinical, electrophysiologic, and genetic data of all patients assessed at our national specialist channelopathy service. Only patients living in the United Kingdom with a genetically defined diagnosis of nondystrophic myotonia or periodic paralysis were eligible for the study. Prevalence rates were estimated for England, December 2011. RESULTS: A total of 665 patients fulfilled the inclusion criteria, of which 593 were living in England, giving a minimum point prevalence of 1.12/100,000 (95% confidence interval [CI] 1.03–1.21). Disease-specific prevalence figures were as follows: myotonia congenita 0.52/100,000 (95% CI 0.46–0.59), paramyotonia congenita 0.17/100,000 (95% CI 0.13–0.20), sodium channel myotonias 0.06/100,000 (95% CI 0.04–0.08), hyperkalemic periodic paralysis 0.17/100,000 (95% CI 0.13–0.20), hypokalemic periodic paralysis 0.13/100,000 (95% CI 0.10–0.17), and Andersen-Tawil syndrome (ATS) 0.08/100,000 (95% CI 0.05–0.10). In the whole sample (665 patients), 15 out of 104 different CLCN1 mutations accounted for 60% of all patients with myotonia congenita, 11 out of 22 SCN4A mutations for 86% of paramyotonia congenita/sodium channel myotonia pedigrees, and 3 out of 17 KCNJ2 mutations for 42% of ATS pedigrees. CONCLUSION: We describe for the first time the overall prevalence of genetically defined skeletal muscle channelopathies in England. Despite the large variety of mutations observed in patients with nondystrophic myotonia and ATS, a limited number accounted for a large proportion of cases.